2017
DOI: 10.1007/s00441-017-2694-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the organisation and phenotypes of bladder interstitial cells in human, mouse and rat

Abstract: With most research on interstitial cells (IC) in the bladder being conducted on animal models, it remains unclear whether all structural and functional data on IC from animal models can be translated to the human context. This prompted us to compare the structural and immunohistochemical properties of IC in bladders from mouse, rat and human. Tissue samples were obtained from the bladder dome and subsequently processed for immunohistochemistry and electron microscopy. The ultrastructural properties of IC were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The relevance of these cells for the physiologic and pathologic function of the bladder has been implied by evidence at several levels. Their strategical positioning at the border between the urothelial layer and the deep lamina propria is accompanied by characteristic receptor expression [7,9] and by the expression of Cx43, leading to the formation of a functional syncytium in vivo [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relevance of these cells for the physiologic and pathologic function of the bladder has been implied by evidence at several levels. Their strategical positioning at the border between the urothelial layer and the deep lamina propria is accompanied by characteristic receptor expression [7,9] and by the expression of Cx43, leading to the formation of a functional syncytium in vivo [43].…”
Section: Discussionmentioning
confidence: 99%
“…The major differences in their distribution define sublayers of the lamina propria, referred to as the upper lamina propria and deeper lamina propria [8]. Recent comparative studies on ICs in human and the major laboratory animals suggest that the understanding of the roles of ICs partly needs revision [7,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Gevaert et al showed in detail the highly similar organization of the interstitial network in the upper and deep lamina propria and the detrusor muscle in human, rat, and mouse bladders [ 137 ]. Despite these extensive similarities of the interstitial phenotypes, several obvious interspecies differences exist, like a predominantly myoid phenotype and contractile micro-filament-enriched lamina propria in the human bladder in comparison with the predominantly fibroblast-like phenotypes found in rat and mouse bladders, which would affect in turn the functional regeneration process.…”
Section: Tissue Engineering For Urinary Bladder Regenerationmentioning
confidence: 99%
“…The interstitial cells of Cajal are better known than the fibroblasts, even if their ultrastructure in the bladder is not well documented (with some important exception, e.g., Ref. 35), and there are many claims about their functional properties and their subtypes (36). The issue of interstitial cells of Cajal in the bladder is presented in several review articles (e.g., Ref.…”
Section: Discussionmentioning
confidence: 99%